2010
DOI: 10.1002/path.2776
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin‐3 is associated with tumour progression and a poor prognosis in nasopharyngeal carcinomas and inhibits cell migration and invasion via suppressed AKT activity

Abstract: Nasopharyngeal carcinoma (NPC) is known for its highly metastatic character. Recent advances in diagnosis and treatment have not improved the high mortality rate that is attributable to early metastasis. Although several biomarkers correlate with metastasis and prognosis, the molecular mechanisms of NPC development and progression remain unclear. We demonstrate comprehensively that fibulin-3 is down-regulated in NPC. Loss of fibulin-3 expression is significantly correlated with advanced tumour and lymph node-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 33 publications
3
83
0
Order By: Relevance
“…Conversely, fibulin-is down-regulated in primary breast tumours, lung cancer and fibrosarcomas (6,14,34) and is thought to inhibit tumour growth. Fibulin-3 is also down-regulated in nasopharyngeal carcinomas and involved in regulation of invasiveness (35). These results suggest that fibulin-3 has dual functions as a positive and negative regulator of cancer cell growth depending on cell type, although its function as a cell modulator is not clearly understood.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, fibulin-is down-regulated in primary breast tumours, lung cancer and fibrosarcomas (6,14,34) and is thought to inhibit tumour growth. Fibulin-3 is also down-regulated in nasopharyngeal carcinomas and involved in regulation of invasiveness (35). These results suggest that fibulin-3 has dual functions as a positive and negative regulator of cancer cell growth depending on cell type, although its function as a cell modulator is not clearly understood.…”
Section: Discussionmentioning
confidence: 97%
“…Although originally characterized as components of elastic fibers in connective tissue, fibulin-3 has been implicated in cell morphology, growth, adhesion, and motility, especially in tumorigenesis [43]. However, current studies conclude that both tumor suppressive functions and oncogenic activities of fibulin-3 can be exhibited in human cancers [44][45][46][47][48]. In 2012, Pass and his colleagues [49] for the first time claimed that fibulin-3 was a highly promising biomarker, which could perform well in the diagnosis and prognosis for MPM.…”
Section: Fibulin-3mentioning
confidence: 93%
“…Previous studies have reported that the EFEMP1 gene plays a role in several types of cancers, such as lung cancer, liver cancer, breast cancer, prostate cancer, and nasopharyngeal cancer (Yue et al, 2007;Sadr-Nabavi et al, 2009;Hwang et al, 2010;Nomoto et al, 2010;Kim et al, 2011;Zhang et al, 2011). Yue et al (2007) reported that alterations in the expression of EFEMP1 could inhibit lung cancer-cell growth, resulting in a high tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…Sadr-Nabavi et al (2009) investigated the role of EFEMP1 in human breast cancer, and reported an association between reduced EFEMP1 expression and the development of sporadic breast cancer and epigenetic alterations. Hwang et al (2010) reported that fibulin-3 could suppress cell migration and invasion in nasopharyngeal cancer cells in a Taiwanese population. Furthermore, Nomoto et al (2010) reported that EFEMP1 was significantly down-regulated in tumor tissues, and that promoter methylation of the EFEMP1 gene could be a marker for the prognosis of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%